PELAKSANAAN PROGRAM PEMBERDAYAAN UMKM DIMASA PANDEMI COVID-19 OLEH DINAS KOPERASI DAN UKM KOTA PEKANBARU TAHUN 2020 - Sofia Dini; Adlin " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2022)
The Covid-19 pandemic that is happening globally, of course, has an impact on various sectors, especially in the economic sector. The Pekanbaru City Government (Pemko) has determined that Pekanbaru is responding to the Covid-19 emergency. . This has an impact on micro, small and medium enterprises (MSMEs) which automatically lose their income due to the restrictions imposed. In Pekanbaru City, around 7,888 Micro, Small and Medium Enterprises (MSMEs) experienced a decline in turnover during the Covid-19 pandemic. In conditions like this, MSME business actors must be able to follow what consumers want. The purpose of the study was to determine the implementation of the UMKM Empowerment Program (BPUM) during the Covid-19 pandemic by the Pekanbaru City Cooperatives and UKM Office based on 4 indicators of policy implementation from George C. Edward III, namely Communication, Resources, Disposition and Bureaucratic Structure. The research method used in this study is a descriptive research method with a qualitative approach. Data collection techniques through interviews, observations, and documentation studies. The problem studied in this study was the MSME Empowerment Program during the Covid-19 Pandemic in Pekanbaru City which was run by the Pekanbaru City Cooperatives and SMEs Office based on the Regulation of the Ministry of Cooperatives and SMEs. The results of this study indicate that the implementation of the MSME empowerment program (BPUM) in Pekanbaru City during the Covid-19 pandemic still did not run according to its goal, namely equal distribution of assistance for all MSME actors. Judging from the Communication indicators, where the implementation has been communicative, from the Resources indicator, the readiness of the planned implementation funds in the APBN is appropriate. Meanwhile, from the Disposition indicator, the policies at the Pekanbaru City Cooperatives and SMEs Office in the context of implementing the program that was launched have not been able to touch the whole community. SMEs in Pekanbaru City because not all SMEs receive BPUM assistance. From the indicators of the bureaucratic structure, the implementation has been very good. Diskop conducts training in accordance with the requirements of good health protocols. The hope in the future is equal distribution of empowerment and assistance for MSME actors affected by the Covid-19 Pandemic. Keywords : Empowerment, SMEs, Covid-19 Pandemic.